TRIPs dalam Kaitannya dengan Perlindungan Hukum Terhadap Rahasia Dagang, Desain Industri dan Desain Tata Letak Sirkuit Terpadu Di Indonesia - Sabri Fataruba (Faculty of Law, Universitas Pattimura, 2020)
Participation in the WTO has given consequences to its member countries, including Indonesia, to harmonize its laws in the field of Intellectual Property Rights for full compliance or full compliance as a minimum requirement and guidelines for WTO member countries to contain new norms and has a higher standard and contains strict law enforcement provisions as set by the TRIPs. In view of these matters, Indonesia has harmonized the existing laws in the field of Intellectual Property Rights and made legal norms in accordance with the standards set by the TRIPs for several fields of Intellectual Property Rights which had not yet been enacted at the time, where 3 ( three) including Law Number 30 of 2000 concerning Trade Secrets, Law Number 31 of 2000 concerning Industrial Design and Law Number 32 of 2000 concerning Layout Designs of Integrated Circuits, the regulations also meet the standards set by TRIPs , in order to provide adequate legal protection to guarantee the rights of Owners of Trade Secrets and Designers and to ensure that other unauthorized parties do not abuse them, so as to motivate the owners of trade secrets and designers to continue to be creative in creating and/or designing, as well also stimulates other communities to do same things.